Yugoslav Hyperinflations and Our Saviors - Popović, Danica (Panoeconomicus, 2022)
This paper overviews hyperinflation episodes in Yugoslavia and elucidates the roles of Prime Minister Ante Marković and Governor Dragoslav Avramović, credited with their successful conclusion. The first part of the paper provides a comparative review of the highest hyperinflations in modern history. The next two parts are dedicated to the role of Ante Marković, in the first, and the role of Dragoslav Avramović during second hyperinflation. The last part of the paper describes the unfavorable final outcome of both hyperinflationary episodes, reveals the causes and indicates the opportunities that were have missed at key moments. Keywords: Hyperinflation, Stabilization policies, Restructuring, Central bank independence. JEL: E31, E58, E65.